Ampliação do sistema agroflorestal da UNESP - Rio Claro/SP: proposta de espaço educativo para formação teórica e prática - Calderón, Nicolas Gabriel da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The UNESP – Rio Claro Campus has an agroforestry system (SAF) implemented in 2010 and managed by the Gira-Sol Agroecology Extension Group. This place is an important training space, however, its structure and development with approximately 12 years, demand specific and more complex managements. Therefore, it is important to have FAS areas with different structures and ages to enhance the experiences of the group and stakeholders. This work aimed to expand the SAF on the campus, conceived as a space for educational practices and university extension activities, as well as a restoring space with a degraded landscape that was used as an area for the disposal of construction waste of the campus. To achieve these objectives, theoretical references and practical knowledge were used, which helped in the planning, implementation and management of the system. The area was divided into two implementation modules, called Module 1 and 2, and the planning, implementation and management processes were recorded with a description of the temporal development of the area and photographic records. The interfaces between theory and practices are discussed, and finally, an area was established that can contribute to the activities and allow group visits. After 1 year and 2 months since the implementation of the SAF, it was verified that there was a possible increase in the photosynthetic capacity of the area, increase in biodiversity, in plant biomass, qualitative improvement of the soil, attraction of fauna and ecological interactions.

O Campus da UNESP – Rio Claro possui um sistema agroflorestal (SAF) implantado em 2010 e manejado pelo Grupo de Extensão em Agroecologia Gira-Sol. Este local é um importante espaço de capacitação, porém, sua estrutura e desenvolvimento com aproximadamente 12 anos, demandam manejos específicos e mais complexos. Com isso, é importante áreas de SAF com diferentes estruturas e idade para potencializar as experiências do grupo e interessados. Este trabalho teve como objetivo a ampliação do SAF no campus concebido como espaço para práticas educativas e atividades de extensão universitária assim como restaurar um espaço com paisagem degradada que foi usado como área de descarte de resíduos de construção do campus. Para atender a esses objetivos foram usados referenciais teóricos e conhecimentos práticos que auxiliaram no planejamento, implantação e manejo do sistema. A área foi dividida em dois módulos de implantação, denominados Módulo 1 e 2, e os processos de planejamento, implantação e manejo foram registrados com a descrição do desenvolvimento temporal da área e registros fotográficos. As interfaces entre teoria e práticas são discutidas, e por fim, se estabeleceu uma área que possa contribuir com as atividades e permita visitas em grupo. Após 1 ano e 2 meses desde a implantação do SAF verificou-se que houve possível aumento na capacidade fotossintética da área, aumento na biodiversidade, na biomassa vegetal, melhora qualitativa do solo, atração de fauna e interações ecológicas.
Expansion of the agroforestry system at UNESP - Rio Claro/SP: proposal for an educational space for theoretical and practical training
Keywords: Agroecology; Agroforestry; Sustainable agriculture; Agricultural ecology; University extension; Agroecologia; Sistemas agroflorestais; Agricultura sustentável; Ecologia agrícola; Extensão universitária